2007
DOI: 10.1111/j.1600-6143.2006.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Sanglifehrin A Blocks Key Dendritic Cell Functions In Vivo and Promotes Long-Term Allograft Survival Together with Low-Dose CsA

Abstract: Sanglifehrin A (SFA) is a novel compound with unsurpassed cyclophilin-binding affinity, but relatively low direct antilymphocytic activity. Here, we report the capacity of SFA to selectively inhibit key dendritic cell (DC) functions in vivo and to suppress acute and chronic heart allograft rejection. We show that in vivo, SFA profoundly decreases DC receptor-mediated endocytosis and macropinocytosis and DC-T-cell allostimulatory activity. Furthermore, SFA abrogates >90% of IL-12p70 production in vivo while hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…DCs are professional APCs that have been shown to be involved in the initiation of the allogenic humoral reaction directed against allografts. [15][16][17] Our study provides further evidence that DCs play a crucial role in transplant arteriosclerosis, as adoptive transfer of alloantigen-primed BMDCs accelerated the disease progression in the mouse aortic allograft model. The data further suggest that HO1 is a key regulator in BMDC function during the alloimmune response in transplantation arteriosclerosis.…”
Section: Discussionmentioning
confidence: 72%
“…DCs are professional APCs that have been shown to be involved in the initiation of the allogenic humoral reaction directed against allografts. [15][16][17] Our study provides further evidence that DCs play a crucial role in transplant arteriosclerosis, as adoptive transfer of alloantigen-primed BMDCs accelerated the disease progression in the mouse aortic allograft model. The data further suggest that HO1 is a key regulator in BMDC function during the alloimmune response in transplantation arteriosclerosis.…”
Section: Discussionmentioning
confidence: 72%
“…In a comprehensive study, SfA was found to suppress antigen uptake and to reduce IL-12 and IL-18 production of DCs in vitro and in vivo without inhibiting the differentiation and surface costimulatory molecule expression of DCs [125][126][127][128]. Immecke et al recently claimed that SfA-mediated suppression of chemokine and CD38 receptor expression in monocyte-derived dendritic cells (moDC) is unique and independent of CyPA [129].…”
Section: Dendritic Cellsmentioning
confidence: 96%
“…In an experimental transplant model, SFA monotherapy did not suppress acute organ allograft rejection supporting the hypothesis that it does not represent a primary T cell inhibitor [11]. Interestingly, in combination with CsA, SFA efficiently promoted long-term allograft survival [11].…”
Section: Introductionmentioning
confidence: 73%